A DIGITAL ECONOMY STRATEGY FOR THE IRAQI ECONOMY - D.r. Kawther Mohammad Duhaim Hassan (Scholar Express Journals, 2024)
The application of the digital economy to the reality of the Iraqi economy requires a set of measures to be taken in order to keep pace with the development in information and communications technology spread in the countries of the developed world, including increasing the efficiency of human cadres working in various sectors and increasing spending on research and development, therefore, the research problem crystallizes around the Iraqi economy, which suffers from various problems in all economic, social and political aspects, has made it unable to keep pace with the development taking place in the field of digital transformation. The application of the digital economy to the reality of the Iraqi economy requires a set of measures to be taken in order to keep pace with the development in information and communications technology spread in the countries of the developed world, including increasing the efficiency of human cadres working in various sectors and increasing spending on research and development, therefore, the research problem crystallizes around the Iraqi economy, which suffers from various problems in all economic, social and political aspects, has made it unable to keep pace with the development taking place in the field of digital transformation.
Keywords: digital Economy; Iraqi economics; communication technology